2012
DOI: 10.1080/02755947.2012.700902
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Adult Spring Chinook Salmon Radio‐Tagged during the Late Stages of Spawning Migration

Abstract: We conducted an experiment to assess the effects of radio‐ tagging on adult spring Chinook salmon Oncorhynchus tshawytscha during the late stages of their spawning migration. Fish were captured at Roza Dam, Yakima River, Washington (river kilometer 208). Each fish had a radio tag inserted into the stomach via the esophagus and was then transported to a raceway and held for 50 d to assess survival. In the same raceway we also held a control group that was handled but not tagged and a group with externally attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(50 citation statements)
references
References 30 publications
3
47
0
Order By: Relevance
“…For wild silver perch (Bidyanus bidyanus) equipped with external tags, more than 50 % of the fish had rejected their external tags within 146 days in tanks or sea-cages [22]. Corbett et al [23] also reported 100 % tag loss during a 50-day laboratory experiment with adult Chinook salmon (Oncorhynchus tshawytscha). Tag loss is not necessarily a negative outcome, because shedding of a tag that becomes snagged in such a way that it would immobilize the fish prevents suffering of the animal [24].…”
Section: Tag Retentionmentioning
confidence: 99%
See 1 more Smart Citation
“…For wild silver perch (Bidyanus bidyanus) equipped with external tags, more than 50 % of the fish had rejected their external tags within 146 days in tanks or sea-cages [22]. Corbett et al [23] also reported 100 % tag loss during a 50-day laboratory experiment with adult Chinook salmon (Oncorhynchus tshawytscha). Tag loss is not necessarily a negative outcome, because shedding of a tag that becomes snagged in such a way that it would immobilize the fish prevents suffering of the animal [24].…”
Section: Tag Retentionmentioning
confidence: 99%
“…Corbett et al [23] compared external tagging with gastric implant for adult Chinook in a 50-day laboratory experiment. Only one of 10 externally tagged salmon died, whereas there was high mortality (19/20) of fish with gastric implants.…”
Section: Survivalmentioning
confidence: 99%
“…; 2.5 min: Corbett et al. ). Also, the environmental conditions in the Harrison River at the time of this study were benign, with normal water flows and water temperatures that were within the predicted optimal thermal window for aerobic scope (Eliason et al.…”
Section: Discussionmentioning
confidence: 99%
“…) and stomach perforation due to presence of the tag in the gastrointestinal tract, which becomes more atrophied the longer a fish spends in freshwater (Dickhoff ; Corbett et al. ). An alternative to gastric insertion is external attachment (Bridger and Booth ).…”
mentioning
confidence: 99%
“…Studies on chinook salmon Oncorhynchus tshawytscha (Walbaum 1792) have shown low survival (10–21%) following gastric insertion of radio tags in both adults (Corbett et al, ) and juveniles (Hall et al, ) relative to untagged controls. Jepsen et al .…”
Section: Number (N) and Mean Fork Length (Lf) Of Salmo Salar Used In mentioning
confidence: 99%